Development of an SDI service for agricultural scientists in the PCARR network - Galang, Lilia S. (1980)
SDI (Selctive Dissemination of Information), a personalized type of current awareness service utilizing electronic data processing techniques was explored by means of an operational experiment. The service was made available to a group of fifteen (15) agricultural scientists undertaking research projects funded by the Philippine Council for Agriculture and Resources Research. Questionnaires and interviews were used to gather data on user's in formation requirements thereby initiating profiles.